2014
DOI: 10.1590/s1517-83822014000300033
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Bacteriocin like inhibitory substance produced by a new Strain Brevibacillus borstelensis AG1 Isolated from 'Marcha'

Abstract: In the present study, a bacterium isolated from Marcha- a herbal cake used as traditional starter culture to ferment local wine in North East India, was evaluated for bacteriocin like inhibitory substance production and was tested against six food borne/spoilage causing pathogens viz. Listeria monocytogenes MTCC 839, Bacillus subtilis MTCC 121, Clostridium perfringens MTCC 450, Staphylococcus aureus, Lactobacillus plantarum and Leuconostoc mesenteroides MTCC 107 by using bit/disc method followed by well diffus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 20 publications
0
8
1
Order By: Relevance
“…Brevibacillus borstelensis is a thermophilic bacteria and was isolated from Kalajoha with a similarity of 100%. It was found previously in, ’Marcha’- a herbal cake used as traditional starter culture to ferment local wine in north-east India and rhizosphere of wheat from northern region of India [25, 26]. But it has not been earlier reported as an endophyte of rice.…”
Section: Discussionmentioning
confidence: 99%
“…Brevibacillus borstelensis is a thermophilic bacteria and was isolated from Kalajoha with a similarity of 100%. It was found previously in, ’Marcha’- a herbal cake used as traditional starter culture to ferment local wine in north-east India and rhizosphere of wheat from northern region of India [25, 26]. But it has not been earlier reported as an endophyte of rice.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al ( 2011a ) identified an anti- C. perfringens lantibiotic produced by Bifidobacterium longum that had a broad range of inhibition. Sharma and colleagues identified a strain of Brevibacillus borstelensis with anti- C. perfringens activity that was associated with a thermostable bacteriocin-like inhibitory substance (BLIS) of 12 kDa, which was active under the physiological conditions expected in the GI tract (Sharma et al, 2014 ).…”
Section: Molecules Of Microbial Originmentioning
confidence: 99%
“…B. borstelensis M9-18 and R. pycnus M9-19 both reduced the mycelial growth of five pathogens (but not P. sulcatum) (Table 4). To the best of our knowledge this is the first report that these bacteria have antagonistic activities against plant pathogens, however it has been reported previously that a strain of B. borstelensis was inhibitory to foodborne microorganisms that include Listeria monocytogenes, B. subtilis, Clostridium perfringens, Staphylococcus aureus, and others (Sharma et al, 2014). P. favisporus did not inhibit any of the tested plant pathogens in our test conditions.…”
Section: Evaluation Of Various Bacterial Antagonists Through General contrasting
confidence: 63%